2018
DOI: 10.1177/0284185118795331
|View full text |Cite
|
Sign up to set email alerts
|

Is MRI an adequate replacement for CT scans in the three-dimensional assessment of acetabular morphology?

Abstract: Background Appropriate three-dimensional imaging of the hip joint is a substantial prerequisite for planning and performing surgical correction of deformities. Although surgeons still use computed tomography (CT), modern and fast acquisition techniques of volumetric imaging using magnetic resonance imaging (MRI) for pelvic measurements enable similar resolution. Purpose This study was designed to determine if already described measures of acetabular morphology are comparable in both techniques and if assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 29 publications
2
37
0
3
Order By: Relevance
“…The differences in ASA may be explained by the difficulty in differentiating between bone and labrum in MRI data, thereby leading to assumed over coverage. The mean differences of ASA were similar to the manual measurements performed by Goronzy et al [8]. Exact measurement of the alpha angle can be demanding in both CT and MRI.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The differences in ASA may be explained by the difficulty in differentiating between bone and labrum in MRI data, thereby leading to assumed over coverage. The mean differences of ASA were similar to the manual measurements performed by Goronzy et al [8]. Exact measurement of the alpha angle can be demanding in both CT and MRI.…”
Section: Discussionsupporting
confidence: 86%
“…These studies focused on static parameters and did not perform intermethod correlation. Goronzy et al investigated manual measurements of acetabular anteversion and coverage of the femoral head and report mean absolute differences not exceeding 0.65° ± 0.86° for inter-and intraobserver as well as intermethod comparison [8]. Chu et al compared manual and fully automatic segmentation of pelvic CT scans and found mean absolute differences of 2.0° ± 1.5° for acetabular version [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although MRI is expensive and sometimes requires sedation, it is still widely used in the examination of immature hips because it does not expose children to radiation and can provide multiplanar, high-quality images that clearly show the boundaries between osseous and cartilaginous structures. A large number of anatomical and MRI studies have shown that MRI can accurately show various morphological changes of the developing hip (Goronzy et al 2019), but few studies have investigated whether MRI is reliable in measuring the OAA and CAA during development. We found excellent consistency between observers, indicating that the repeatability of MRI measurement is high.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the advantage of noninvasively distinguishing the osseous rim from the cartilaginous acetabulum in the immature hip, magnetic resonance imaging (MRI) has been widely used to evaluate the pathological abnormity of DDH (Mootha et al 2010, Krasny et al 1991, Falliner et al 2002, Douira-Khomsi et al 2010, Goronzy et al 2019. In this retrospective cross-sectional MRI study we measured OAA and CAA in children of various ages using MRI, analyzed their Background and purpose -Acetabular anteversion (AA) is related to hip function.…”
mentioning
confidence: 99%